The Effect of Organizational Learning and Transformational Leadership on Employee Performance with Job Satisfaction as A Mediation Variable - Evi Komala; Rr. Erlina Erlina; Zainnur M. Rusdi (MASI Mandiri Edukasi, 2026)
This study aims to analyze the effect of organizational learning and transformational leadership on the performance of civil servants in Bandar Lampung City, with job satisfaction serving as a mediating variable. The results of the data analysis indicate that organizational learning has a positive and significant effect on civil servant performance, suggesting that a strong learning culture and mastery of technology enhance employee performance. Transformational leadership is found to have a significant, negative direct effect on performance, suggesting that its effectiveness depends on support from other mechanisms. Furthermore, job satisfaction has been shown to play a significant mediating role in the relationships between organizational learning and performance, as well as between transformational leadership and performance. These findings emphasize that improving civil servant performance is not solely determined by structural and leadership factors, but is also strongly influenced by employee job satisfaction. Therefore, public organizations need to manage organizational learning processes and leadership styles in a balanced manner to sustainably enhance job satisfaction and employee performance.